2020
DOI: 10.1101/2020.09.16.299842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sexually dimorphic influence of the circadian clock geneBmal1in the striatum on alcohol intake

Abstract: SummaryThe clock gene Bmal1 plays an obligatory role in the generation of circadian rhythms in gene expression, physiology, and behavior in mammals [1–4]. In mice, perturbations in Bmal1 expression in the brain are associated with loss of circadian rhythmicity and various physiological and behavioral disturbances, including disrupted sleep architecture and deficits in cognitive and affective behaviors [5–14]. Gene association studies in both humans and animals suggest that Bmal1 may also play a role in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…The result of our study suggests that binge drinking was significantly reduced in animals following antisense‐induced downregulation of clock genes in the NAcSh, suggesting that a causal relationship exists between circadian genes in the NAcSh and binge drinking in C57BL/6J mice. Supporting our results, previous study has demonstrated that the knockdown of Per2 gene selectively in the dorsal and ventral striatum reduced alcohol consumption (Zavalia et al, 2020). Additionally, the involvement of these circadian genes was also investigated in regard to other substance of abuse.…”
Section: Discussionsupporting
confidence: 91%
“…The result of our study suggests that binge drinking was significantly reduced in animals following antisense‐induced downregulation of clock genes in the NAcSh, suggesting that a causal relationship exists between circadian genes in the NAcSh and binge drinking in C57BL/6J mice. Supporting our results, previous study has demonstrated that the knockdown of Per2 gene selectively in the dorsal and ventral striatum reduced alcohol consumption (Zavalia et al, 2020). Additionally, the involvement of these circadian genes was also investigated in regard to other substance of abuse.…”
Section: Discussionsupporting
confidence: 91%
“…Sections containing the SCN were identified and immunohistochemically stained for either the circadian clock-gene, BMAL1 (1:30,000; made in rabbit, polyclonal, Novus Biologicals, NB100-2288), or p75NTR, a marker of retinal connectivity (1:8,000; made in rabbit, polyclonal, Millipore Sigma #07-476). The use, antibody specificity and quantification of BMAL1 has previously been described by others (Gall et al, 2003;Wyse and Coogan, 2010;Al-Safadi et al, 2014;de Zavalia et al, 2021). In brief, the primary antibody solution was made in a milk buffered (5%) triton-TBS solution and 2% normal goat serum and incubated for 48 h at 4 • C. After rinsing the free-floating tissue in TBS, a secondary incubation solution containing biotinylated anti-rabbit IgG made in goat (1:200 dilution; Vector Laboratories, Burlington, ON, Canada) was used.…”
Section: Tissue Preparation and Immunohistochemistrymentioning
confidence: 99%